Mikrofinanse nowym wyzwaniem Unii Europejskiej (aspekt humanistyczny) - Mikołajczyk, Bożena (Annales. Etyka w Życiu Gospodarczym, 2009)
Microfinance is intended to combat the phenomenon of social and financial exclusion. We hope that the supportive political environment in the EU will meaningfully contribute to the betterment of this situation in Europe. The paper draws attention to the banking and non-banking institutions granting microloans which constitute the key element facilitating the creation and continued operation of firms. It is very important that microfinance is viewed as a weapon in the fight against poverty and inaccessibility of financial services.